Effect of Maternal Triclosan Exposure on Neonatal Birth Weight and Children Triclosan Exposure on Children's BMI: A Meta-Analysis - Liu, Jiani; Chen, Danrong; Huang, Yanqiu; Bigambo, Francis Manyori; Chen, Ting; Wang, Xu (Frontiers in Public Health, 2021)
Background: Triclosan(TCS) is an environmental chemical with endocrine disrupting effects and can enter the body through the skin or oral mucosa. Human data about the effect of TCS exposure during pregnancy on neonatal birth weight and TCS exposure during childhood on children's growth are scarce. Objectives: To investigate the association between maternal urinary TCS level and neonatal birth weight, as well as children's urinary TCS level and children's BMI(Body Mass Index). Methods: A systematic literature search was conducted using PubMed, Cochrane Library, and Web of Science. Finally, seven epidemiological articles with 5006 participants from September 25th, 2014 to August 10th, 2018 were included in the meta-analysis to identify the relationship between maternal exposure to TCS and neonatal birth weight. On the other hand, three epidemiological articles with 5213 participants from July 22th, 2014 to September 1st, 2017 were included in another meta-analysis to identify the relationship between children's exposure to TCS and children’s BMI. We used Stata 16.0 to test the heterogeneity among the studies and calculating the combined effect value 95%CI(95 percent confidence interval) of the selected corresponding models. Results: TCS exposure during pregnancy was not significant associated with neonatal birth weight. The results of forest plots were as follows: ES (Estimate) =0.41, (95%CI: -11.97–12.78). Children's urinary TCS level was also irrelevant associated with children's BMI: ES=0.03, (95%CI: -0.54–0.60). Conclusions: This meta-analysis demonstrated that there was no significant association between maternal TCS level and neonatal birth weight, also there has no relationship between children's urinary TCS level and children's BMI.